Hubungan Kecanduan Game Online Terhadap Kualitas Tidur dan Kecenderungan Perilaku Agresif pada Remaja di SMP Negeri 3 Taliabu Utara - Ana Julianti (Indo Publishing, 2026)
Online game addiction needs to be addressed as early as possible, as delays can negatively impact students, such as sleep disturbances and a tendency toward aggressive behavior in daily life. This study aims to determine the relationship between online game addiction and sleep quality and the relationship between online game addiction and aggressive behavior in adolescents at SMP Negeri 3 Taliabu Utara. This study used a quantitative research method with a correlational design. The sampling technique used nonprobability sampling, with a sample size of 64 students from a population of 174. Data were analyzed using the Pearson product-moment correlation test. The results of this study show a significant value of online game addiction with aggressive behavior of 0.000 and online game addiction with sleep quality of 0.793. The significance value of online game addiction with aggressive behavior is less than 0.05 (<0.05) indicating that there is a significant relationship between the two variables. The significance value of online game addiction with sleep quality is greater than 0.05 (>0.05) indicating that there is no significant relationship between the two variables. As for suggestions for further researchers, it is recommended to consider the use of variables influenced by online game addiction and use other methods to gain a deeper understanding of the impact of online game addiction on adolescents.